Prevalence of and risk factors for high-altitude hyperuricaemia in Bai individuals: a cross-sectional study. Issue 7 (July 2021) - Gao, Chenni; Chen, Zijin; Ma, Jun; Xie, Jingyuan; Zhang, Wen; Ren, Hong; Chen, Xiaonong
Objective: Hyperuricaemia is common in Bai individuals; however, its prevalence remains unclear. This work aimed to investigate high-altitude hyperuricaemia prevalence and risk factors in Bai individuals. Methods: All eligible participants of Bai ethnicity (aged ≥18 years and undergoing routine medical examination at the People's Hospital of Jianchuan County between January and December 2019) were consecutively enrolled. Demographic and laboratory data were collected to investigate hyperuricaemia prevalence and associated risk factors. Results: A total of 1393 participants were assessed, comprising 345 (24.8%) with hyperuricaemia showing a male predominance (287/865 [33.2%] males versus 58/528 [11.0%] females). Hyperuricaemia prevalence was significantly higher in participants aged ≥50 years (100/332 [30.1%]) versus those aged 30–40 years (59/308 [19.2%]), and in overweight/obese individuals compared with those showing an underweight or normal body mass index (BMI; 267/885 [30.2%] versus 78/508 [15.4%]). Finally, haemoglobin concentrations and serum uric acid levels were positively correlated. Conclusion: Besides traditional risk factors, including age, sex and BMI, polycythaemia due to prolonged exposure to high altitude may also cause hyperuricaemia in Bai individuals residing in Yunnan Province.